Facile hydrothermal reduction synthesis of porous Co3O4 nanosheets@RGO nanocomposite and applied as a supercapacitor electrode with enhanced specific capacitance and excellent cycle stability. (20th December 2016) - Du, Feng; Zuo, Xueqin; Yang, Qun; Li, Guang; Ding, Zongling; Wu, Mingzai; Ma, Yongqing; Jin, Shaowei; Zhu, Kerong
Abstract: A facile hydrothermal reduction synthesis has been proposed to fabricate porous Co3 O4 nanosheets anchored on reduced graphene oxide (Co3 O4 @RGO). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images reveal that the Co3 O4 nanosheets are porous and dispersed on RGO films. The supercapacitor based on Co3 O4 @RGO nanocomposite electrode reaches a higher specific capacitance of 894 F g −1 which is about three times higher than the pure Co3 O4 electrode (300 F g −1 ) at the current density of 1 A g −1 . In addition, both electrodes demonstrate remarkable long-term cycle life, especially for the Co3 O4 @RGO nanocomposite, which shows almost no obvious attenuation after 3000 cycles. The superior performance indicates that, due to the exceptional structure characteristics between Co3 O4 nanosheets and RGO films, the composite possesses both higher specific capacitance and long-term cycle stability.